Criminal Sanctions for Severe Assault against Unmarried Women in the Perspective of Islamic Law - Ade Sultan Muhammad; Ika Yuliana Susilawati (Yayasan pendidikan dzurriyatul Quran, 2026)
Violence against women in Indonesia, particularly in the form of severe assault, continues to increase and causes significant physical and psychological impacts. This study aims to analyze the perspective of Fiqh Jinayah on severe assault against unmarried women (ghairu muhsan) and to examine the relevance of sanctions in Indonesian positive law from the perspective of Maqashid Sharia. This research employs a normative legal method using statute, conceptual, and comparative approaches, based on library research of primary, secondary, and tertiary legal sources. The findings indicate that Islamic criminal law provides a more comprehensive approach through the mechanisms of Qisas, Diyat, and Ta’zir, integrating retributive, restorative, and reconciliatory aspects. In contrast, Indonesian positive law tends to emphasize punitive justice through imprisonment. Furthermore, Islamic law places victims in a central position, including the right to grant forgiveness, thus offering a more victim-oriented approach. Despite these differences, both legal systems share the same objective of protecting human life (hifz an-nafs). This study concludes that integrating restorative justice values from Fiqh Jinayah into the national criminal law system could enhance justice and strengthen victim protection